Examination of Machining Parameters on the Surface Roughness of Stavax ESR Materials using EDM - Mebrahitom, A.; Azmir, Azhari (Trans Tech Publications, Switzerland, 2014)
An experimental study was conducted to investigate the effect EDM die sinking machining parameters on surface roughness of Stavax material for mould insert. The spark gap, peak current and servo voltage were manipulated to find the best combination of EDM machining parameters. The surface roughness of the machined surface of each specimen was measured using Perthometer and the image of texture was observed by using optical microscope. It was observed that the surface roughness was highly affected by the spark gap and peak current whereas the servo voltage had little effect.